Cardiac arrhythmia in patients with inflammatory bowel disease: a retrospective, population-based cohort study in Manitoba, Canada - Charles N Bernstein; Zoann Nugent; Mariam Narous; Inna Rabinovich-Nikitin; Lorrie Kirshenbaum (BMJ Open)
Objective We aimed to characterise the association between inflammatory bowel disease (IBD) and IBD medications and risk of cardiac arrhythmia.Design, setting and participants In a retrospective population-based study using the University of Manitoba IBD Epidemiology Database (Manitoba, Canada) from 1984 to 2018, we identified 10 992 IBD cases and 102 875 matched controls.Analysis Arrhythmia risk in IBD was adjusted for the presence of comorbidities of the Charlson Comorbidity Index. The effect of IBD medications on the development of arrhythmia was assessed in a nested cohort study of individuals with IBD. Cases were censored at the date of first database identification of a diagnosis of heart failure or myocardial infarction.Results The cohort was 48.5% Crohn’s disease and 51.5% ulcerative colitis, and 80.5% were incident cases. The median age of incident cases at IBD diagnosis was 35 (IQR, 25 to 49). The median age at arrhythmia diagnosis for persons with IBD was 69 years (IQR, 59 to 77) and for controls 69 years (IQR, 59 to 78). Persons diagnosed with IBD were more likely than controls (HR 1.51; 95% CI, 1.30 to 1.76) to develop arrhythmia. Persons within their sixth decade or younger had increased risk of arrhythmia. When controlling for comorbidities, the significant association between IBD and arrhythmia remains. Medications including 5-aminosalicylates, thiopurines and tumour necrosis factor-α inhibitors were not associated with arrhythmia.Conclusions Persons with IBD have a higher risk of arrhythmia prior to a diagnosis with heart disease. Use of IBD medications was not associated with risk of arrhythmia.